AIAA Scitech 2020 Forum 2020
DOI: 10.2514/6.2020-2290
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Dynamic Behavior of a High Aspect Ratio Wing Incorporating a Folding Wingtip

Abstract: High aspect ratio wings have been the focus of recent aircraft designs for improving fuel efficiency through induced drag reduction. The lengthened wingspan derived from these designs have led to the introduction of folding wingtips in order to meet airport gate width requirements. Previous numerical and experimental studies have demonstrated that folding wingtips can also provide a gust load alleviation benefit, when the folding wingtips are able to rotate freely about the hinge during the gust encounter. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Using a model with the locked hinge, the distribution of both CBEAM elements and concentrated masses along the wing were optimised to closely match the modal frequencies, below 15 Hz, previously measured with the experimental model at a wind speed velocity of 18 ms −1 [17].…”
Section: A Baseline Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a model with the locked hinge, the distribution of both CBEAM elements and concentrated masses along the wing were optimised to closely match the modal frequencies, below 15 Hz, previously measured with the experimental model at a wind speed velocity of 18 ms −1 [17].…”
Section: A Baseline Modelmentioning
confidence: 99%
“…Whilst the wingtips of the 777X can only be operated on the ground, the inclusion of such a mechanism raises the question as to whether folding wingtips can be utilised in-flight for aerodynamic or structural benefits. One such solution is the Flared Folding Wingtip (FFWT) [8][9][10][11][12][13][14][15][16][17][18]. As illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the achieved reduction from the wind tunnel measurements is higher than predicted. Cheung et al 15,16 added an aerodynamic surface into the wingtip to control the folding action. In a series of steady aerodynamic tests, they demonstrated that this device is capable of maintaining the orientation of the wingtip over a range of wind tunnel velocities and angles of attack.…”
Section: Introductionmentioning
confidence: 99%
“…Figure16. Comparison of the shear force-torsional moment convex hull obtained with the wingtip rigidly connected to the wing and the wingtip free to rotate.…”
mentioning
confidence: 99%
“…. 9 1.7 Wing in the wind tunnel in a free-hinge configuration (directly adapted from [7] 1.9 Tethered flight test of the AlbatrossOne model (directly adapted from [8]). 14 1.10 Discrete-gust approach to design (directly adapted from [9]).…”
Section: Titlementioning
confidence: 99%